Exploring the Path of Personal Information Infringement Governance by Web Crawlers - Yan Liu; Ping Zheng; Yutong Li; Mengxuan Li; Xin Zhang (Studies in Law and Justice, 2024)
In the era of big data, the explosive growth of data information, network crawler as a new type of data search engine came into being, and gradually become indispensable technology. However, with the continuous penetration of crawler technology, related infringement problems have gradually surfaced. This topic starts from the definition and technical application of network crawlers, further analyzes the specific forms of network crawlers’ personal information infringement, and discusses and summarizes the shortcomings of the legal governance measures involved, and finally draws on the experience of overseas and combines the views of relevant scholars, proposes to improve the relevant legal provisions and clarify the division of responsibility; introduces the rule of balanced trial; establishes the criteria for the reasonable use of data by crawlers; creates a “cyclical protection system”; establishes the “data protection system”; and establishes the “data protection system”. The proposal to establish a cyclical protection system, establish a “data protection officer”, set up an independent regulatory body, form an internal and external linkage mechanism, and then build a scientific governance system for scientific governance.